2009
DOI: 10.1063/1.3078107
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable high effective work function TaCN thin films for metal gate electrode applications

Abstract: TaCN layers were deposited using metal-organic chemical-vapor deposition for applications as metal gate electrodes in p-type metal-oxide-semiconductor (pMOS) devices. The films were formed by thermal decomposition of tertiary-amylimido-tris(dimethylamido)tantalum (TAIMATA®) between 400 and 600 °C. The composition was dependent on the growth temperature with increasing C and decreasing N content at higher temperature. Films grown below 500 °C were nearly amorphous and became weakly polycrystalline with a cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Ta nitride ALD was also reported using a range of metal-organic precursors, such as Ta-based alkylamides and alkylimides such as pentakis (dimethylamido) tantalum [PDMAT, Ta(NMe 2 ) 5 ], 12 6,23 Basically, the use of metalorganic precursors has benefits in producing halogen-free films.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Ta nitride ALD was also reported using a range of metal-organic precursors, such as Ta-based alkylamides and alkylimides such as pentakis (dimethylamido) tantalum [PDMAT, Ta(NMe 2 ) 5 ], 12 6,23 Basically, the use of metalorganic precursors has benefits in producing halogen-free films.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6] Although the main applications of these materials are as a diffusion barrier for copper metallization, [1][2][3][4][5] they are also considered to be a metal gate with high-permittivity gate dielectrics. 6 For these applications, they need to be deposited uniformly at high aspect ratio (AR) structures with a conformal thickness as the demand for shrinking dimensions is increased. In addition, a deposition technique with high process controllability and large-area uniformity is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that as the nitrogen content increases, an optically transparent and electrically insulating phase appears to form [31]. The work function of Hf films is around 4.1 eV [11], whereas that of HfN x films is between 4.55 and 4.9 eV [11,24,32]. The work function of HfN x appears to be dependent on the nitrogen content and the interface properties of HfN x /gate dielectrics.…”
Section: Introductionmentioning
confidence: 91%
“…The three key points for selection of gate electrode materials are work function, thermal stability, and lower resistivity. So far, many types of materials have been investigated to replace poly-silicon, such as pure metals [2][3][4][5][6], binary alloys [7][8][9][10], metal nitrides [11][12][13][14][15], metal carbides [16], and fully silicided Si (FUSI) [17][18][19][20]. Of these, the refractory transition metal nitrides are of interest owing to their good thermal stability, good oxygen diffusion barrier characteristics, and tunable work function.…”
Section: Introductionmentioning
confidence: 99%